Capacity Building for Elementary School Teachers in the Implementation of Science Literacy through Outreach Using an Environment-Based STEAM Approach - Prastyaningrum, Ihtiari; Alfina, Alisa; Dhemahestri, Melta; Muhammad Iqbal S. M. (Jurnal Inovasi Sains dan Teknologi Untuk Masyarakat, 2026)
Science literacy is an important competency in 21st-century learning because it is related to the ability to understand scientific concepts and apply them in everyday life. However, students' science literacy skills are still relatively low, partly due to the teacher-centered learning process and the suboptimal use of the environment as a learning resource. Therefore, efforts are needed to improve teachers' capacity in designing contextual and innovative learning. This community service activity aims to improve elementary school teachers' capacity to apply science literacy learning through an environment-based STEAM approach. This community service activity was carried out at Kwadungan Public Elementary School using several stages, namely needs analysis, material socialization, STEAM paradigm reconstruction, science literacy workshops, environmental exploration, and activity evaluation. The results of the activity show that before the activity was carried out, most teachers did not understand the concept of STEAM learning and did not optimally utilize the surrounding environment as a learning resource. After participating in the socialization and training activities, teachers began to understand the basic concepts of STEAM and were able to identify the potential of the environment as a contextual learning resource. Thus, this activity contributed to improving teachers' capacity in terms of understanding, knowledge, and skills in designing innovative and contextual science literacy learning.